Epidemiology and outcome of paediatric out-of-hospital cardiac arrests: A paediatric sub-study of the Pan-Asian resuscitation outcomes study (PAROS). (April 2018) - Tham, Lai Peng; Wah, Win; Phillips, Rachel; Shahidah, Nur; Ng, Yih Yng; Shin, Sang Do; Nishiuchi, Tatsuya; Wong, Kwanhathai Darin; Ko, Patrick Chow-In; Khunklai, Nalinas; Naroo, Ghulam Yasin; Ong, Marcus Eng Hock
Abstract: Background: The Pan Asian Resuscitation Outcomes Study (PAROS) is a retrospective study of out- of-hospital cardiac arrest(OHCA), collaborating with EMS agencies and academic centers in Japan, South Korea, Malaysia, Singapore, Taiwan, Thailand and UAE-Dubai. The objectives of this study is to describe the characteristics and outcomes, and to find factors associated with survival after paediatric OHCA. Methods: We studied all children less than 17 years of age with OHCA conveyed by EMS and non-EMS transports from January 2009 to December 2012. We did univariate and multivariate logistic regression analyses to assess the factors associated with survival-to-discharge outcomes. Results: A total of 974 children with OHCA were included. Bystander cardiopulmonary resuscitation rates ranged from 53.5% (Korea), 35.6% (Singapore) to 11.8% (UAE). Overall, 8.6% (range 0%–9.7%) of the children survived to discharge from hospital. Adolescents (13–17 years) had the highest survival rate of 13.8%. 3.7% of the children survived with good neurological outcomes of CPC 1 or 2. The independent pre-hospital factors associated with survival to discharge were witnessed arrest and initial shockable rhythm. In the sub-group analysis, pre-hospital advanced airway [odds ratio (OR) = 3.35, 95% confidence interval (CI) = 1.23–9.13] was positively associated with survival-to-discharge outcomes in children less than 13 years-old. Among adolescents, bystander CPR (OR = 2.74, 95%CI = 1.03–7.3) and initial shockable rhythm (OR = 20.51, 95%CI = 2.15–195.7) were positive factors. Conclusion: The wide variation in the survival outcomes amongst the seven countries in our study may be due to the differences in the delivery of pre-hospital interventions and bystander CPR rates.